An evaluation of the quality care for type 2 diabetes patients in the primary healthcare using the lot quality assurance sampling technique - Ali Kazemiathar; Hosein Azizi; Parvin Bastani; Fariba Abbasi; Elham Davtalab Esmaeili; Sheida Ghorbani; Shahriyar Ghanbarzadeh Javid (BMC, 2024)
Abstract Background Diabetes is the most prevalent metabolic disease globally. Correct and effective healthcare management requires up-to-date and accurate information at the local level. This level of information allows managers to determine whether the health system has achieved its desired goals in this area. This study aimed to evaluate the adequacy and quality of care for Type 2 diabetes mellitus (T2DM) patients using the Lot quality assurance sampling (LQAS) technique to provide evidence for decision-making at the local level, prioritizing and allocating resources. Methods A descriptive-analytical study was conducted in 12 supervision areas (SAs)/health facilities in northwestern Iran involving 240 patients with T2DM in primary health care. The selection of patients and determination of SAs were done randomly using the LQAS technique. Glycated Hemoglobin (HbA1c) was used to evaluate patients' blood sugar control in each SA. Multiple linear regression analysis was used to estimate predictors of HbA1c in T2DM. Results The overall average of HbA1c value was 7.84%. The HbA1c level was > 7% in 148 (61.6%) of the patients. Among the 12 SAs, the LQAS identified unacceptable quality of care in 5 SAs. In the final analysis, each unit increase in fasting blood sugar (FBS), High-density lipoprotein (HDL), Low-density lipoprotein (LDL), and Thyroglobulin (TG) values resulted in an increased in HbA1c levels by 0.43, 0.183, 0.124, and 0.182 times, respectively. However, with a one-unit increase in the care of a family physician and nutritionist, along with regular physical activity, HbA1c levels decreased by − 0.162, -0.74, and − 0.11 times, respectively. Conclusions The quality of care for diabetic patients needs improvement in some SAs. Findings indicated that the LQAS technique effectively identifies centers/areas with substandard diabetes care quality and efficiently allocates resources to those in need. It is recommended to implement corrective measures in areas with inadequate care quality.